Kontribusi Motivasi Belajar Dan Kreativitas Terhadap Kemandirian Belajar Santri Kulliyatul Muallimin Al-Islamiyah Pondok Pesantren Ta'mirul Islam Surakarta Tahun 2016/2017 - Prayitno, Bakti, Prof. Dr. Bambang Sumardjoko, M.Pd, Dr. Waston, M.Hum (2017)
The purpose of this study, there are three: first, to determine the magnitude of the percentage of learning motivation of the students learning independence. second, To determine the percentage of creativity in learning to students learning independence. Third, To determine the percentage of learning motivation and creativity with the same students towards independent learning. Quantitative research, research design ex-post facto by the correlation technique. Research conducted at KMI Ta'mirul Surakarta Islamic boarding school in the first semester of the school year 2016/2017 with a sample of 105 students. The sampling technique using proportional random sampling using kracjie table. Data collection techniques in this study using questionnaires and observation. Data analysis techniques used in this study multiple regression analysis after previously performed classical assumption as normality test, linearity test, test multicollinearity, heteroscedasticity test and autocorrelation test. The results of this study there are three, (1) there is a significant contribution to the learning motivation 0.05 on independent learning and give students the effective contribution of 23.97%. (2) there is a significant contribution to the study of creativity 0.05 on independent learning and give students the effective contribution of 39.94%. (3) there is a significant contributions are learning motivation and creativity together in a significant 0.05 on students learning independence by 63.2%. So there are still 36.8% more other variables not included in this study.